SARIMA-Orthogonal Polynomial Curve Fitting Model for Medium-Term Load Forecasting - Herui Cui; Pengbang Wei; Yupei Mu; Xu Peng (Discrete Dynamics in Nature and Society)
Seasonal component has been a key factor in time series modeling for medium-term electric load forecasting. In this paper, a seasonal-ARIMA model is developed, but the parameters of the SAR and the SMA turn out to be quite nonsignificant in most cases during the model order selection. To address this issue, the hybrid time series model based on the HP filter is utilized to extract the spectrum sequences with different frequencies and analyze interactions among various factors. Finally, an integrative forecast is made for the electricity consumption from January to November in 2014. The empirical results demonstrate that the method with HP filter could reduce the relative error caused by the interaction between the trend component and the seasonal component.